2023
DOI: 10.1111/acel.14040
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell‐specific reduction in mTOR ameliorates age‐related arterial and metabolic dysfunction

Md Torikul Islam,
Shelby A. Hall,
Tavia Dutson
et al.

Abstract: Systemic inhibition of the mammalian target of rapamycin (mTOR) delays aging and many age‐related conditions including arterial and metabolic dysfunction. However, the mechanisms and tissues involved in these beneficial effects remain largely unknown. Here, we demonstrate that activation of S6K, a downstream target of mTOR, is increased in arteries with advancing age, and that this occurs preferentially in the endothelium compared with the vascular smooth muscle. Induced endothelial cell‐specific deletion of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…We have recently demonstrated that endothelial-specific reduction in mTOR improves age-related arterial and metabolic dysfunction. 13 Others have shown that EC-specific inactivation of a transcription factor, NF-κB, or tumor suppressor, p53, attenuates HF diet–induced metabolic dysfunction. 17,40 Reduction in inflammatory signals prevents obesity-induced impairments in the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently demonstrated that endothelial-specific reduction in mTOR improves age-related arterial and metabolic dysfunction. 13 Others have shown that EC-specific inactivation of a transcription factor, NF-κB, or tumor suppressor, p53, attenuates HF diet–induced metabolic dysfunction. 17,40 Reduction in inflammatory signals prevents obesity-induced impairments in the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a recent study, we have found that endothelial mTOR (mammalian target of rapamycin) deletion improves arterial and metabolic function in old mice. 13 Together, these studies suggest that endothelial-specific inflammatory mediators can be a target for arterial dysfunction and associated metabolic dysfunction. In a series of studies in the last decade, Arf6 (ADP ribosylation factor 6) has been described as an inflammatory mediator in the vascular endothelium, although its role in arterial and metabolic function remains largely unknown.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…30 On the contrary, improvement in endothelium-dependent dilation in old mice lacking mammalian target of rapamycin specifically in endothelial cells was shown to ameliorate glucose and lipid tolerance and attenuate hepatic gluconeogenesis. 31 Dysfunction of sinusoidal endothelial cells in the liver has been implicated in the progression of nonalcoholic fatty liver disease via numerous mechanisms, including dysregulation of the inflammatory process, activation of hepatic stellate cells, augmentation of vascular resistance, and distortion of the microcirculation, resulting in the progression of nonalcoholic fatty liver disease. 32,33 Cardiac Influence on Systemic Metabolism…”
Section: Vascular Effects On Metabolismmentioning
confidence: 99%